Design Team Perception of Development Team Composition: Implications for Conway's Law - Burton, S. H.; Bodily, P. M.; Morris, R. G.; Knutson, C. D.; Krein, J. L. (2011 Second International Workshop on Replication in Empirical Softwre Engineering Research, 2011)
Conway's law, the idea that a software system reflects the structure of the organization that built it, is one of the most well-known "laws" in software engineering. However, the seemingly straightforward phenomenon described by Conway appears to be subject to nuances of personal and organizational dynamics as well as contextual factors, most of which are neither well-understood nor well-studied. As a pilot study intended to foster discussion within the RESER community, we performed a small and somewhat informal qualitative study designed to elucidate some of these nuances. We posited that the designers' perception of the ultimate composition of the development team would affect the resultant system architecture more so than would the actual composition of the design team. The results of the pilot study support this hypothesis and are intended as a motivator for on-going discussion, as well as a catalyst for more thorough and formal differentiated replications, to explore and elucidate the nuances of Conway's law.